The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1007/s11141-007-0078-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiometer of the 3-mm wave range with a modulator-calibrator

Abstract: We describe a radiometer intended for use in the spectroradiometric complex for remote sensing of the Earth's atmosphere. The main feature of the radiometer is application of an electrically controlled modulator-calibrator allowing one to perform measurements and thermal calibration in a wide temperature range without using matched loads and means for their connection. The principle of operation and design of the modulator-calibrator are described and the characteristics of the radiometer and its separate unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 4 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…As a result of the measurements using superheterodynes [1,8], it is shown that at a frequency of 115 GHz, the effective temperature of radiation from the large aperture of the developed device varies from room temperature to 650 K (see Fig. 3) as a current from 0 to 3 mA flows via the diode matrix.…”
Section: Measurement Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result of the measurements using superheterodynes [1,8], it is shown that at a frequency of 115 GHz, the effective temperature of radiation from the large aperture of the developed device varies from room temperature to 650 K (see Fig. 3) as a current from 0 to 3 mA flows via the diode matrix.…”
Section: Measurement Resultsmentioning
confidence: 99%
“…The effective temperature decreases almost monotonically with increasing frequency to almost 310 K for a current of 3 mA in the region of 300 GHz. The effective temperature drop to below room temperature, which was observed for small currents in the SBD modulator-calibrators [1][2][3], was not observed in the described case of the δ-doped diodes.…”
Section: Measurement Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, an electrically controlled device for internal calibration of the spectroradiometer (modulator-calibrator) developed at the Institute of Applied Physics of the Russian Academy of Sciences in cooperation with the "NIIPP" Company was included between the antenna and the receiver [9]. This device ensures antenna connection to the receiver input with a loss of about 0.5 dB (for a zero current) or input of the noise calibration signal depending on the current through the circuits of Schottky-barrier diodes (SBDs) built in the waveguide section.…”
Section: Hardwarementioning
confidence: 99%